Oncogene-Induced Senescence as a New Mechanism of Disease: The Paradigm of Erdheim–Chester Disease - Cavalli, Giulio; Biavasco, Riccardo; Borgiani, Bruno; Dagna, Lorenzo (Frontiers in Immunology, 2014)
Erdheim-Chester disease (ECD) is a rare form of systemic histiocytosis characterized by the diffuse infiltration of tissues by lipid-laden macrophages. As the clinical course and prognosis are highly influenced by site of disease involvement, ECD course ranges from asymptomatic to life threatening, with a reported global 5-year mortality of 30-40%. Whether ECD is a inflammatory or clonal disease in its nature has long been debated. The disease is characterized by a network of pro-inflammatory cyto/chemokines responsible for the recruitment and activation of histiocytes into ECD lesions, similarly to what reported in Langerhans cell histiocytosis (LCH). Growing evidence supports a central role of the oncogenic BRAFV600E mutation in histiocytosis pathogenesis, and suggests oncogene-induced senescence (OIS), a major protective mechanism against oncogenic events characterized by cell-cycle arrest and the induction of pro-inflammatory molecules, as the possible link between the oncogenic mutation and the observed inflammation. Indeed ECD recapitulates in vivo the molecular events associated with OIS, i.e. cell-cycle arrest and a potent local inflammatory response. Accordingly, the infiltration of different tissues by macrophages and the inflammatory local and systemic effects observed in ECD likely represent a drawback of OIS. Therefore, these findings delineate a new conception of OIS as a new pathogenic mechanism intrinsically responsible for disease development.